Effectiveness of the 6-month BPaLM regimen in a patient with rifampicin-monoresistant tuberculosis - Joy January A. S. Ninu; Nikson Eduard Faot (Institute for Advanced Science, Social, and Sustainable Future, 2026)
Background: Tuberculosis (TB) is an infectious disease caused by the bacterium Mycobacterium tuberculosis and remains a global health problem, including in Indonesia. Rifampicin-resistant tuberculosis (TB) (RR-TB) is a form of anti-tuberculosis drug resistance in which Mycobacterium tuberculosis only shows resistance to rifampicin, without resistance to isoniazid or other first-line drugs. The combination of Drug Resistant Tuberculosis (TB RO) treatment regimens greatly influences the effectiveness of TB RO patient treatment management. The purpose of this study was to see the effectiveness of the 6-month BPaLM regimen in a patient with rifampicin-monoresistant tuberculosis in Sabu Raijua Regional Hospital, Sabu Raijua Regency, East Nusa Tenggara. Methods: This type of research is a quantitative study with a cross-sectional approach to see the effectiveness of the 6-month BPaLM regimen in a patient with rifampicin-monoresistant tuberculosis at Sabu Raijua Regional Hospital in 1 case treated from the beginning of treatment (baseline), monthly follow-up and until the end of treatment. Findings: The study results show that the BPaLM regimen is highly effective in eradicating RR-TB in patients in areas with limited facilities, such as the 3T (terpencil, terluar, dan tertinggal/ disadvantaged, frontier, and outermost) areas. Multidisciplinary clinical, laboratory, and radiological monitoring are key to successful therapy, including early detection of side effects and ensuring adherence. Therefore, this 6-month BPaLM regimen is highly effective in assisting in the management of RR-TB treatment. Conclusion: In conclusion, the 6-month BPaLM regimen demonstrates high effectiveness in treating rifampicin-monoresistant tuberculosis (RR-TB), even in limited-resource settings such as disadvantaged, frontier, and outermost areas. Comprehensive multidisciplinary monitoring is essential to ensure treatment success and patient adherence. Novelty/Originality of this article: This study provides new evidence of the successful implementation of the 6-month BPaLM regimen for rifampicin-monoresistant tuberculosis (RR-TB) in a remote, limited-resource setting (disadvantaged, frontier, and outermost area), demonstrating its practicality and effectiveness beyond controlled or urban healthcare environments.